Implementation of Interprofessional Health Education-based Research Based on Discipline, Practice, Dissemination Trends and Research Design: A Literature Review - Nurkholis, Fiqih (KIAN JOURNAL, 2023)
Objective: The World Health Organization (WHO) started a program in 2007 to promote Interprofessional Education (IPE) and its benefits for collaborative practice. Many IPE reviews have examined what has been done and how effective it is. This review aimed to investigate the methods and outcomes of IPE research. Methods: IPE research examined the following: 1) disciplines involved; 2) writing patterns, 3) assessment focus, and 4) dissemination trends. Abstracts were screened prior to full-text screening, review, data extraction, analysis and audit. Categorical data were reported with frequencies and percentages while continuous data were reported with means and standard deviations. Chi-square analysis was used to test for differences between groups for categorical variables. Results: Of the 359 articles that met the criteria, most were written by authors from medical, nursing, and pharmacy schools, using quantitative or mixed techniques. Most studies involved student disciplines with no authors from those disciplines. Most studies also measured student perceptions and knowledge, with a few measuring faculty perceptions. Research was mostly conducted in classrooms, simulations, and field experiences. IPE research was published in 98 journals, most of which were interdisciplinary journals, with the largest increase in publications in the last year of the review. Conclusions: The field of IPE research has grown significantly in the last decade. It is important to explore different ways to conduct IPE research, plan ways to disseminate IPE results, and ensure that all disciplines of students involved in IPE are represented in authorship.